OPTIMALISASI PEMBIAYAAN PENDIDIKAN DI TENGAH DISPARITAS FISKAL : STUDI SMAN 1 LONG BAGUN - Anggy Hanggara; Norkumala Dewi; Arie EkaYudhistira Kirana Tejawati; Winaryati; Widyatmike Gede Mulawarman; Mukhamad Nurhadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the optimization of educational financing in the context of fiscal disparities, focusing on SMAN 1 Long Bagun in Mahakam Ulu Regency, a frontier, outermost, and disadvantaged (3T) area in Indonesia. The study addresses the challenges arising from unequal regional fiscal capacity, high operational costs due to geographical constraints, and limited managerial capacity in resource utilization. The objective of this research is to analyze how the school plans, allocates, and manages its financial resources, identify the constraints faced, and formulate adaptive and contextual financing strategies. This study employs a qualitative approach with a case study design, using purposive sampling to select key informants such as the principal, school treasurer, and school committee. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that fiscal disparities significantly influence the effectiveness of educational financing, where most of the budget is allocated for basic operational needs due to high logistical costs. Despite these limitations, the school demonstrates adaptive strategies through prioritization and efficient resource management. However, limited flexibility in budget use and low innovation in alternative funding remain key challenges. The study concludes that effective educational financing in 3T areas requires not only sufficient funding but also adaptive management, strengthened institutional capacity, and context-sensitive policy support to ensure equitable education quality.